PERLINDUNGAN KONSUMEN DALAM PENJUALAN BARANG DAGANGAN TIDAK SESUAI TIMBANGAN BERDASARKAN UNDANG-UNDANG NOMOR 8 TAHUN 1999 TENTANG PERLINDUNGAN KONSUMEN - Hafas, Muhammad; Fatahillah, Fatahillah; Kurniasari, Tri Widya (Jurnal Ilmiah Mahasiswa Fakultas Hukum Universitas Malikussaleh, 2025)
The rapid development of the economy has resulted in many productions of goods and services that can be easily consumed by consumers. With increasing competition in traditional markets, it is not uncommon to find dishonest traders, for example, in weighing, measuring, and calculating. This research aims to analyze consumer protection in the sale of goods that do not comply with weighing standards based on Law Number 8 of 1999 concerning Consumer Protection and the government's efforts to overcome the sale of goods that do not comply with weighing standards. The research method used is a normative juridical approach, which is a legislative approach. The data sources in this writing are primary legal materials, secondary legal materials, and tertiary legal materials. Based on the research results, consumer protection is found in Article 4 letter c of Law Number 8 of 1999 concerning Consumer Protection, which explains the right of consumers to obtain transparency and accurate and reliable information from business actors. The efforts made are to conduct supervision by the Metrology Agency over traders in the use of weighing instruments and their equipment. It is hoped that the government will not only supervise the use of weighing instruments and other equipment but also encompass the morals and behavior of traders. It is also hoped that the general public, especially traders, will uphold the value of honesty.